2018
DOI: 10.1111/famp.12384
|View full text |Cite
|
Sign up to set email alerts
|

“I Just Kept It to Myself”: The Shaping of Latina Suicidality Through Gendered Oppression, Silence, and Violence

Abstract: Suicide is a critical issue among Latina youth. In this study, we use family case analysis to explore how gendered oppression, silencing, and violence shape suicidal behaviors among a sample of Latina daughters (n = 10), and their parents. For comparison, we include family narratives from Latina adolescents with no histories of suicide attempts (n = 10). Results suggest how secrets and silence, as indicative of gendered oppression, may catalyze a suicide attempt. The risks are particularly salient when daughte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…Several aspects of family functioning have been linked to Latina adolescent suicidal behaviors, including parental support, family response to stress, disruptions in family structure, and familial violence (De Luca, Wyman, & Warren, 2012; Gulbas et al, 2011, 2015; Peña et al, 2011; Szlyk, Gulbas, & Zayas, 2018; Turner, Kaplan, Zayas, & Ross, 2002). A study of a national sample of 1,618 Latina high‐school students found that suicidal ideation was associated with lower perceived father support, and attempt with lower perceived family support (De Luca et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…Several aspects of family functioning have been linked to Latina adolescent suicidal behaviors, including parental support, family response to stress, disruptions in family structure, and familial violence (De Luca, Wyman, & Warren, 2012; Gulbas et al, 2011, 2015; Peña et al, 2011; Szlyk, Gulbas, & Zayas, 2018; Turner, Kaplan, Zayas, & Ross, 2002). A study of a national sample of 1,618 Latina high‐school students found that suicidal ideation was associated with lower perceived father support, and attempt with lower perceived family support (De Luca et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In gender and/or sexual minority oriented studies, children were considered oppressed because of their gender and/or sexuality. In an American Latino context, this gendered oppression was manifested by silencing and violence through intergenerational experiences, shaping suicidal behaviors in Latina teenagers (Szlyk et al, 2019). Another population of concern is LGBTQ youth.…”
Section: Resultsmentioning
confidence: 99%
“…The accounts served as analytical cases through which I could explore Netflix's promotional practices on Twitter (e.g. Szlyk et al , 2019). I sampled tweets from August 30, 2019, to December 31, 2019, which amassed a corpus of 1,432 tweets.…”
Section: Methodsmentioning
confidence: 99%